35,000 registered missing in 13 years of conflict as ICRC helps families seek answers - International Committee of the Red Cross (International Committee of the Red Cross, 2024)
In the past 13 years, the ICRC has registered 35,000 cases of people who have gone missing in Syria. This number reflects the requests of the families who approached the ICRC - we know that in reality the numbers are far greater.

Pakistan: Training journalists on fact-checking in a humanitarian crisis - International Committee of the Red Cross (International Committee of the Red Cross, 2023)
Factual and responsible reporting by the media can help affected communities cope better by enhancing their knowledge, connecting them with first responders, highlighting their needs and providing access to authorities.
Keywords: 2023-08 August